ASME 2015 Gas Turbine India Conference 2015
DOI: 10.1115/gtindia2015-1369
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis of Effect of Diffuser Vane Setting Angle and Shape on the Performance of a Centrifugal Compressor Stage

Abstract: This paper describes the computational results on the performance of a centrifugal compressor stage with Vaneless diffuser (VLD) and low solidity vaned diffuser (LSVD) by varying blade shape and its setting angle. The centrifugal compressor stage configuration consists of a 2-D impeller with a diffuser. Analysis was conducted for VLD and four different blade shapes of LSVD namely Un-cambered constant thickness flat plate (FP), Cambered curved arc constant thickness plate (CCAP), Un-cambered aerofoil profile NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…19 Regarding the abnormal blade, the LES (Large Eddy Simulation) simulation of axial fan conducted by Li et al 20 indicated that the increase of blade stagger angle led to significant increase of entropy production and transitions of discrete peak of acoustic noise from a low-frequency region to a high-frequency region. In Boccazzi et al’s 21 and Pothuri’s 22 works, highest losses were found for the vaned diffuser with the most tangential setting angle. Meanwhile, the radial velocity component and absolute flow angle with low setting angle were more uniformly distributed along the span compared with those with large setting angles.…”
Section: Introductionmentioning
confidence: 94%
“…19 Regarding the abnormal blade, the LES (Large Eddy Simulation) simulation of axial fan conducted by Li et al 20 indicated that the increase of blade stagger angle led to significant increase of entropy production and transitions of discrete peak of acoustic noise from a low-frequency region to a high-frequency region. In Boccazzi et al’s 21 and Pothuri’s 22 works, highest losses were found for the vaned diffuser with the most tangential setting angle. Meanwhile, the radial velocity component and absolute flow angle with low setting angle were more uniformly distributed along the span compared with those with large setting angles.…”
Section: Introductionmentioning
confidence: 94%